Broken promises agrarian reform and the Latin American Campesino - Thiesenhusen, William C. (Westview Press, 1995)
"Critically examines successes and failures of agrarian reform efforts in Bolivia, Chile, El Salvador, Guatemala, Nicaragua, and Mexico. Concludes that agrarian reform has done little to reduce poverty or to create employment opportunities and a more equal distribution of resources. Worth reading"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/